REKONSTRUKSI POLITIK HUKUM KETAHANAN PANGAN BERBASIS SISTEM KEARIFAN LOKAL GUNA MEWUJUDKAN KEDAULATAN PANGAN - Rachmad Syafa’at; Esmi Warrasih Pujirahayu; Aan Eko Widiarto (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2012)
The existence of the Tengger Traditional Community wisdom system in Ngadas Village, Malang Regency managing food crops agriculture and natural resources is partly apparent, developed, and continuous until now. The main problem of his study is how to set up a political law reconstruction model of local Tengger Traditional Community wisdom based food sustainability for establishing food sovereignty. The study utilizes two approach methods, the first being the normative approach is to analyze various law regulations, policies, and political laws related with statewide food sustainability and the implementations on the Tengger customs society. Meanwhile, the socio legal approach is to examine the presence of the local wisdom system and noticeable conflicts in the natural resource management experienced by the Tengger Traditional Community. The findings from this research reveal that the co-management model implementation are required to share commitment among the government and the public to be equally open, responsible, and strengthen their participation in a local wisdom system based food sustainability political law reconstruction in order to establish food sovereignty, either on the national, provincial, as well as city / regency level.